PERFORMANCE INVESTIGATION OF AN ELECTRO ADSORPTION CHILLER - Chu, Kai Jing (2018)
Environment pollution is unavoidable if the current refrigeration system available nowadays is sustained. In this report, probability of green technologies which are adsorption chiller and thermoelectric system as approach to replace the existing cooling system have been discussed. Adsorption chiller uses waste heat which can be solar driven as the source to perform cooling. The adsorption-refrigerant pairs are discussed and chosen. Thermoelectric cooling system creates cooling and heating junction by using peltier effect and have benefits when size is matter compared to adsorption chiller. A novel, high cooling density and low maintenance cooling system is highly requested to solve the heat dissipating issue which the chiller is miniaturized and fit onto the desktop of the PC or the server system. A novel miniaturized chiller is proposed which cascades the adsorption chiller and thermoelectric cooling devices which known as electro-adsorption chiller. This proposed system is to overcome the low efficiency of individual. The performance of the electro adsorption chiller is investigated by using Matlab modelling and simulation. All the results and discussion will be recorded in the dissertation write up. The working principles for adsorption chiller, thermoelectric cooling, electro-adsorption chiller and other areas such as adsorbent-refrigerant pairs have been studied. The COP of the proposed adsorption chiller can reach up to 1.35 approximately and it successfully exceeds the both individual cycle of adsorption chiller and thermoelectric cycle with COP range 0.1-0.6 and 0.1-0.4 respectively.